Patterns of Ganglion Cell Complex and Nerve Fiber Layer Loss in Nonarteritic Ischemic Optic Neuropathy by Fourier-Domain Optical Coherence Tomography - Aggarwal, Divya; Tan, Ou; Huang, David; Sadun, Alfredo A. (Investigative ophthalmology & visual science, 2012)
To characterize by Fourier-domain optical coherence tomography (FD-OCT) the loss of nerve fiber layer (NFL) and ganglion cell complex (GCC) in nonarteritic ischemic optic neuropathy (NAION). Patients diagnosed with NAION were enrolled and categorized into "superior field loss (SFL)," "inferior field loss (IFL)," and "bihemispheric field loss (BFL)" groups based on the Swedish interactive threshold algorithm 30-2 achromatic visual field (VF) tests. Six months after presentation, they were scanned by FD-OCT to map peripapillary NFL and macular GCC thicknesses. Age-matched normals were selected from participants in the Advanced Imaging for Glaucoma Study (www.AIGStudy.net). Deviation maps were defined as the difference between the thickness maps and the average normal maps. Pearson's correlation coefficient was used to assess the correlation between VF and OCT measurements. Twenty-five NAION eyes in 20 subjects were analyzed. Most (2/3) SFL cases showed inferior NFL loss with variable sparing of inferonasal losses. All (4/4) IFL cases showed superior NFL loss with variable inferonasal extension. The GCC maps demonstrated clear hemispheric loss pattern in agreement with VFs. NFL and GCC losses could be detected even in the less affected hemispheres (P < 0.001). NFL and GCC were highly correlated (P < 0.001) with VF in terms of both overall averages and superior-inferior hemispheric differences. NFL and GCC losses correlated well with VF losses in both magnitude and location. Hemispheric GCC loss correlated with altitudinal VF loss and this pattern may be of diagnostic value. FD-OCT is useful in the evaluation of NAION.